2001
DOI: 10.1515/bc.2001.138
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Highly Specific Serine Endopeptidase from an Oral Strain of Staphylococcus epidermidis

Abstract: Infection by Staphylococcus epidermidis, an opportunistic pathogen, has become a major problem due to the increased use of implanted medical devices and the growing number of patients who are therapeutically or infectiously immunosuppressed. These infections appear to proceed via modulation of the coagulation and complement systems. In this communication we describe the purification and characterization of a novel extracellular proteinase from an oral strain of S. epidermidis that can degrade fibrinogen, compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 21 publications
(24 reference statements)
0
45
0
Order By: Relevance
“…The negligible rate of hydrolysis of Suc-Ala-Ala-Pro-AsppNA by Ϫ1 S-SprE versus the good activity of the enzyme against Suc-Ala-Ala-Pro-Glu-pNA was similar to that of GluSE of S. epidermidis (36) and argues for the fact that SprE does not tolerate an Asp residue at the P1 site. On the other hand, the lack of turnover of Z-Leu-Leu-Glu-pNA, in contrast to Z-Phe-Leu-Glu-pNA results, strongly indicated that enzyme specificity was modulated by the S3 subsite substrate-binding pocket, which apparently could not accommodate a branched aliphatic chain of the Leu residue.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The negligible rate of hydrolysis of Suc-Ala-Ala-Pro-AsppNA by Ϫ1 S-SprE versus the good activity of the enzyme against Suc-Ala-Ala-Pro-Glu-pNA was similar to that of GluSE of S. epidermidis (36) and argues for the fact that SprE does not tolerate an Asp residue at the P1 site. On the other hand, the lack of turnover of Z-Leu-Leu-Glu-pNA, in contrast to Z-Phe-Leu-Glu-pNA results, strongly indicated that enzyme specificity was modulated by the S3 subsite substrate-binding pocket, which apparently could not accommodate a branched aliphatic chain of the Leu residue.…”
Section: Discussionmentioning
confidence: 82%
“…On the other hand, the lack of turnover of Z-Leu-Leu-Glu-pNA, in contrast to Z-Phe-Leu-Glu-pNA results, strongly indicated that enzyme specificity was modulated by the S3 subsite substrate-binding pocket, which apparently could not accommodate a branched aliphatic chain of the Leu residue. This narrow specificity of SprE is surprising, since with the exception of the preference for Glu at the P1 position, its close homologues, V8 and GluSE (12,36,57), are rather indiscriminant. It is even more interesting, however, that none of the other forms of the SprE proteinase was able to cleave any of the tested synthetic substrates, even though they were active on protein substrates such as insulin, fibrinogen, and casein.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…SspA and SspB are transcribed on a single polycistronic mRNA that is regulated by the Agr and Sar systems (6,17). SspA is homologous to the S. aureus V8 protease (65% identity), which is an important virulence factor (17,38,39) that possibly interferes with complement activation and blood coagulation (17,38). SspB is homologous to both of the S. aureus staphopain cysteine proteases SspB1 and SspB2 (61% and 75% identical, respectively) and has been shown to degrade human immunoglobulins, serum albumin, fibronectin, and all three subunits of fibrinogen, which might contribute to immune system avoidance and the establishment and/or dissemination of infection (52).…”
Section: Discussionmentioning
confidence: 99%
“…GluV8 processes adhesion molecules that are expressed on the bacterial cell surface and destroy the extracellular matrix of host cells (Karlsson & Arvidson, 2002). GluSE was found as an S. epidermidis GluV8 homolog, which is the most abundant extracellular protein (Sasaki et al, 1998), and efficiently degrades host proteins such as elastin, fibronectin, collagen, complement protein C5, and immunoglobulin (Dubin et al, 2001;Moon et al, 2001;OharaNemoto et al, 2002). The gene encoding GluSE is ubiquitously distributed on the chromosome and the protein is expressed in most clinical isolates under in vitro culture conditions (Fig.…”
Section: Staphylococcal Glutamic Acid-specific Proteasementioning
confidence: 99%